Influence of Back Pain on Patient Satisfaction Scores. Issue 6 (June 2015) - Shirley, Eric D.; Mohamed, Ahmed S.; Neal, Kevin
<x xml:space="preserve">Abstract</x> Objectives Patient satisfaction scores are increasing in importance. Although the influence of selected patient and physician characteristics on satisfaction scores has been identified, the impact of different pediatric diagnoses is unknown. The purpose of this study was to compare patient satisfaction scores in visits for mechanical back pain with visits for clubfoot or scoliosis. Methods A retrospective analysis of patient satisfaction scores from pediatric visits for back pain, clubfoot, and scoliosis at three tertiary centers was performed. Satisfaction data were obtained from survey questions that used a 5-point scale ranging from very poor (1) to very good (5). Statistical analysis was performed using χ2 and Fisher exact tests. Results Data from 565 visits for scoliosis, 81 for clubfoot, and 57 for mechanical back pain were used. The mean scores in back pain visits for the likelihood of recommending the care provider, confidence in the care provider, and explanation by the care provider were 4.87, 4.79, and 4.70, respectively. These scores were not lower than visits for scoliosis and clubfoot (P < 0.05). The mean score for likelihood to recommend the practice after back pain visits was 4.73, with more scores of 3 or higher than clubfoot or scoliosis (P < 0.05). Conclusions Satisfaction scores in pediatric patients with back pain were not lower than visits for scoliosis or clubfoot. Future research can be directed toward identifying common goals in visits for pediatric mechanical back pain to further improve the patient experience.